2009
DOI: 10.3409/fb58_1-2.85-90
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of TCDD Dioxin on the Rat Liver in Biochemical and Histological Assessment

Abstract: Eighteen male Wistar rats were divided into 3 groups of 6 animals each. Two groups received different intraperitoneal doses of TCDD (0.75 and 8Fg) in DMSO solution and the third group (control) received only DMSO on days 0, 7 and 14. On day 21 the animals were sacrificed, and then blood tests, pathological examination and CYP1A1 activity measurement were performed. In rats that received a high dose of dioxin (8 Fg) hepatic lobules revealed parenchymal degeneration and vacuolization of hepatocytes was observed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 19 publications
6
27
0
Order By: Relevance
“…Besides, our study demonstrated that TCDD treatment caused severe histological damages (numerous apoptotic cells and vacuolated hepatocytes) in the liver tissues of rats. These results are in agreement with some previous studies (Patterson et al,2003; Czepiel et al,2010). From our results, it is clear that TCDD treatment at doses of 2 μg/kg/week for 60 days induced lipid peroxidation, histological damage, and reduced antioxidant system activity in rat liver.…”
Section: Discussionsupporting
confidence: 94%
“…Besides, our study demonstrated that TCDD treatment caused severe histological damages (numerous apoptotic cells and vacuolated hepatocytes) in the liver tissues of rats. These results are in agreement with some previous studies (Patterson et al,2003; Czepiel et al,2010). From our results, it is clear that TCDD treatment at doses of 2 μg/kg/week for 60 days induced lipid peroxidation, histological damage, and reduced antioxidant system activity in rat liver.…”
Section: Discussionsupporting
confidence: 94%
“…It has been reported that the pathological effects of TCDD in hepatic tissue may lead to the disruption in the functional integrity of hepatocytes (Czepiel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our finding, MTT assay demonstrated that the viabilities of human adrenocortical, pancreatic and mammary cells were significantly decreased after TCDD treatment (McDougal et al 1997;Bradshaw et al 2002;Koliopanos et al 2002;Andersson et al 2005. It is reported that the detrimental effects in hepatic tissue of TCDD may lead to disruption in the functional integrity of hepatocytes (Sakamoto et al 1995;Boverhof et al 2006;Czepiel et al 2010;Kopec et al 2010). Thus, TCDD is known to be responsible for the carcinogenic effects associated with oxidative DNA damage (Hung et al 2006).…”
Section: Discussionmentioning
confidence: 99%